2015
DOI: 10.1021/acs.jpcb.5b05401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Na+–Cl Ion-Pair in Water–Methanol Mixtures under Supercritical and Ambient Conditions

Abstract: Constrained molecular dynamics simulations have been performed to investigate the structure and thermodynamics of Na(+)-Cl(-) ion-pair association in water-methanol mixtures under supercritical and ambient conditions in dilute solutions. From the computed potentials of mean force (PMFs) we find that contact ion pairs (CIPs) are more stable than all other associated states of the ion pairs in both ambient and supercritical conditions. Stabilities of CIPs increase with increase in the mole fraction of methanol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 97 publications
(172 reference statements)
2
2
0
Order By: Relevance
“…As a result, CIPs, SAIPs, and SSIPs are more stable in supercritical conditions compared to those in ambient conditions. This has been previously observed in ion pair association studies by several authors. ,, Because the decrease in the dielectric constant facilitates ion association, one may expect the contact ion pair to be more stable in the 5.55 m solution in supercritical conditions, but in reality, we observe the opposite. There is hardly any decrease in the dielectric constants as we go from the 0.27 m (∼3.47) to 5.55 m solution (∼3.30) in the supercritical conditions.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As a result, CIPs, SAIPs, and SSIPs are more stable in supercritical conditions compared to those in ambient conditions. This has been previously observed in ion pair association studies by several authors. ,, Because the decrease in the dielectric constant facilitates ion association, one may expect the contact ion pair to be more stable in the 5.55 m solution in supercritical conditions, but in reality, we observe the opposite. There is hardly any decrease in the dielectric constants as we go from the 0.27 m (∼3.47) to 5.55 m solution (∼3.30) in the supercritical conditions.…”
Section: Resultssupporting
confidence: 80%
“…For the Cl − ion, the anion−oxygen peak is centered at 0.33 nm, which is in good agreement with that deduced from MD simulations 5,6,28,29,78,81 and from X-ray diffraction studies. The first peaks of the Cl − −O (H 2 O) radial distribution functions are centered at around 0.33 nm in both the thermodynamic states under study.…”
Section: Ion-solvent Radial Distribution Functionssupporting
confidence: 88%
See 1 more Smart Citation
“…For simple salts in water–dimethyl sulfoxide (DMSO) mixtures, it was observed that sodium ions are preferentially solvated by water molecules, whereas chloride ions favor a coordination by DMSO, which stands in sharp contrast to the corresponding donor numbers of the solvents in pure solution . Furthermore, it was observed that sodium chloride reveals a homoselective preferential solvation behavior by water molecules in water–methanol and DMSO–acetonitrile (AN) solutions, , as well as in water–AN mixtures . For more complex organic ions, recent simulations of DMSO–water mixtures also revealed a homoselective solvation mechanism, where water molecules form the first solvation shell around both ion species.…”
Section: Introductionmentioning
confidence: 99%